Form-deprivation myopia downregulates calcium levels in retinal horizontal cells in mice. (May 2022) - Li, Qihang; Zhu, He; Fan, Miaomiao; Sun, Jing; Reinach, Peter S.; Wang, Yuhan; Qu, Jia; Zhou, Xiangtian; Zhao, Fuxin
Abstract: The process of eye axis lengthening in myopic eyes is regulated by multiple mechanisms in the retina, and horizontal cells (HCs) are an essential interneuron in the visual regulatory system. Wherein intracellular Ca 2+ plays an important role in the events involved in the regulatory role of HCs in the retinal neural network. It is unknown if intracellular Ca 2+ regulation in HCs mediates changes in the retinal neural network during myopia progression. We describe here a novel calcium fluorescence indicator system that monitors HCs' intracellular Ca 2+ levels during form-deprivation myopia (FDM) in mice. AAV injection of GCaMP6s, as a protein calcium sensor, into a Gja10-Cre mouse monitored the changes in Ca 2+ signaling in HC that accompany FDM progression in mice. An alternative Gja10-Cre/Ai96-GCaMP6s mouse model was created by cross mating Gja10-Cre with Ai96 mice. Immunofluorescence imaging and live imaging of the retinal cells verified the identity of these animal models. Changes in retinal horizontal cellular Ca 2+ levels were resolved during FDM development. The numbers of GCaMP6s and the proportion of HCs were tracked based on profiling changes in GCaMP6s + calbindin + /calbindin + coimmunostaining patterns. They significantly decreased more after either two days ( P < 0.01) or two weeks ( P < 0.001) in form deprived eyes than in the untreated fellow eyes. These decreases in their proportion reached significance only in the retinal central region rather than also in the retinal periphery. A novel approach employing a GCaMP6s mouse model was developed that may ultimately clarify if HCs mediate Ca 2+ signals that contribute to controlling FDM progression in mice. The results indicate so far that FDM progression is associated with declines in HC Ca 2+ signaling activity. Highlights: FDM downregulates calcium level in horizontal cells either two days or two weeks. Downregulation of Ca 2+ in horizontal cells is region-specific only in the retinal center. GCaMP6 mouse model can clarify HCs mediate Ca 2+ signals that contribute to controlling FDM.